2012
DOI: 10.1039/c2jm15350e
|View full text |Cite
|
Sign up to set email alerts
|

Zinc (hydr)oxide/graphite based-phase composites: effect of the carbonaceous phase on surface properties and enhancement in electrical conductivity

Abstract: Composites of zinc hydroxide with graphite-oxide and graphite derived material are prepared using in situ precipitation of Zn(OH) 2 in the presence of the dispersed graphite-based phases. The new materials are characterized by a range of methods, including SEM, infrared and Raman spectroscopy, thermal analysis, potentiometric titration, nitrogen adsorption, XPS, and electrical measurements. The results indicate that the final properties of the composites are determined by a complex interplay between the two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…Bandosz and co-workers [2] have shown that such materials exhibit the photo-activity in the visible light [3]. The determination of the optical band gap is important because it not only controls the efficiency for solar conversion and the shape of the optical emission spectrum, but also manifests the effect of structural and thermal disorder on the electronic properties of the nano-composites [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bandosz and co-workers [2] have shown that such materials exhibit the photo-activity in the visible light [3]. The determination of the optical band gap is important because it not only controls the efficiency for solar conversion and the shape of the optical emission spectrum, but also manifests the effect of structural and thermal disorder on the electronic properties of the nano-composites [4].…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 300 • C can be assigned to the decomposition of the strongly adsorbed CEES and/or HEES [32,33]. Finally, the weight loss that occurred above 760 • C is linked to the removal of ZnCl 2 species [34] and/or to the reduction of zinc oxide to Zn (boiling point 907 • C) by the carbonaceous phase [8]. The traces of the latter phase might be formed during the thermal analysis (charring of organic compounds).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the adsorptive performance, as well as the photocatalytic properties of the zinc oxide are well known [8,9], the hydrated oxides have attracted less attention, even though they have been reported as superior to oxide in certain applications [10]. The latter is owing to the high reactivity of their OH groups, especially terminal ones, with specific adsorbates.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, graphite oxide (GO) with metal oxide composites have been extensively studied as adsorbents [16][17][18]. Graphite oxide-based or graphene-based materials are known to be useful for water purification, toxic gas removal and ammonia adsorption applications [19][20][21].…”
Section: Introductionmentioning
confidence: 99%